Consumption Taxes and Corporate Investment - Jacob, Martin; Michaely, Roni; Müller, Maximilian A (Review of Financial Studies, 2019)
Abstract Consumers nominally pay the consumption tax, but theoretical and empirical evidence is mixed on whether corporations partly shoulder this burden, thereby affecting corporate investment. Using a quasi-natural experiment, we show that consumption taxes decrease investment. Firms facing more elastic demand decrease investment more strongly, because they bear more of the consumption tax. We corroborate the validity of our findings using 86 consumption tax changes in a cross-country panel. We document two mechanisms underlying the investment response: reduced firms’ profitability and lower aggregate consumption. Importantly, the magnitude of the investment response to consumption taxes is similar to that of corporate taxes. Received September 25, 2017; editorial decision August 26, 2018 by Editor Wei Jiang. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.